Situation Report: Bulgaria, 29 January 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Todor Zhivkov Ends Visit to India Bulgarian-Yugoslav Controversies Flare Up Again Report on 1968 Economic Plan Fulfillment Bulgarian-Soviet Technological Agreement Signed